Organic laser diodes: modelling and simulation - Gärtner, Christian (KIT Scientific Publishing, 2009)
This thesis analyzes the impact of various loss processes on the threshold current density of organic semiconductor laser diodes by numerical simulation. Design concepts based on organic double-heterostructures are evaluated and design rules are derived which can be used in order to reduce the impact of loss processes and in order to improve the device performance.